Organisaation oppiminen sosiaali- ja terveydenhuolto-organisaatioissa – Kollektiivinen reflektio käytännön strategiatyössä - Korin Heidi; Liikamaa Kirsi (Finland, 2025)
This research explores how collective reflection during strategizing supports organizational learning. Strategizing evolves over time as strategy practitioners interact with each other, use different strategy practices, and gain more experience of their strategy work. However, this learning process and the meaning of collective reflection within it has not been given attention in previous research. The theoretical frame of the study consists of strategy-as-practice (SAP), collective reflection, and organizational learning literature. In particular, the 4I-framework of organizational learning developed by Crossan et. al. (1999) is utilized. The empirical data were collected by a survey. According to the findings of the study, collective reflection during strategizing supports organizational learning, which, during strategizing, proceeds through microprocesses of intuition, interpretation, integration, and institutionalization. Furthermore, the study shows that the 4I model is suitable for scrutinizing organizational learning during strategizing.